2006
DOI: 10.1002/chin.200604200
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from the Indian Ocean Gorgonian Subergorgia suberosa (Pallas).

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Fatty acids cause an increase in membrane fluidity which results in a generalized disorganization of the cell membrane that leads to conformational changes in membrane proteins, the release of intracellular components, cytoplasmic disorder, cell disintegration and eventually cell death (Pohl et al, 2011). In addition to fatty acids, ethanamines (Thvedt et al, 2013), pregnane and its derivatives (Yoon et al, 2011;Subrahmanyam et al, 2005), pyrimidine and its derivatives (Sharma et al, 2014;Neumann et al, 2014), myrtenol (Tabassum and Vidyasagar, 2013) have also been reported to show antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids cause an increase in membrane fluidity which results in a generalized disorganization of the cell membrane that leads to conformational changes in membrane proteins, the release of intracellular components, cytoplasmic disorder, cell disintegration and eventually cell death (Pohl et al, 2011). In addition to fatty acids, ethanamines (Thvedt et al, 2013), pregnane and its derivatives (Yoon et al, 2011;Subrahmanyam et al, 2005), pyrimidine and its derivatives (Sharma et al, 2014;Neumann et al, 2014), myrtenol (Tabassum and Vidyasagar, 2013) have also been reported to show antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies on the Subergorgia gorgonians against microorganisms and macrofouling organisms, the crude extract from S. suberosa possessed inhibitory effects on fungi and no effects from S. mollis were observed at the tested concentrations (Koh et al , 2002). Further work showed that subergorgic acid, thymine and N-hexadecanoyl-2-amino-1,3-dihydroxyoctadec-4-ene isolated from the gorgonian S. suberosa exhibited antibacterial and antifungal activities (Subrahmanyam et al , 2005). Moreover, the effective inhibition of subergorgic acid and progesterone on larval settlement of B. amphitrite and B. neritina were observed (Qi et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[26] A formulation was developed for the isolation of a sesquiterpene ketone, which is claimed to inhibit the growth of tumor cells and treat breast cancer, leukemia, oral cancer, liver cancer, and lung cancer. [27]…”
Section: Chemical Constituents and Biological Activitiesmentioning
confidence: 99%
“…Examinations of the gorgonian sea coral S. suberosa collected from the Mandapam coast, resulted in the identification of four compounds, batyl alcohol, subergorgic acid N-hexadecanoyl-2-amino-1,3-dihydroxyoctadec-4-ene, and thymine. [ 26 ] A formulation was developed for the isolation of a sesquiterpene ketone, which is claimed to inhibit the growth of tumor cells and treat breast cancer, leukemia, oral cancer, liver cancer, and lung cancer. [ 27 ]…”
Section: Chemical Constituents and Biological Activitiesmentioning
confidence: 99%